2017
DOI: 10.1371/journal.pone.0176323
|View full text |Cite
|
Sign up to set email alerts
|

The performance of BD FACSPresto™ for CD4 T-cell count, CD4% and hemoglobin concentration test in Ethiopia

Abstract: IntroductionIn Ethiopia, CD4+ T-cell counting is still required for all patients at baseline before antiretroviral therapy (ART) and to determine eligibility and follow-up of opportunistic infection prophylaxis. However, access to CD4+ T cell count in rural health facilities remains a major challenge in Ethiopia like other resource-limited settings.MethodologyBoth capillary and venous blood was drawn from each of 325 study participant recruited in Addis Ababa and surroundings. The CD4+ T-cell count, CD4%, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…Reliable CD4 count testing is needed in health facilities to monitor the immune status of PLHIV, even as access to VL monitoring expands. This study found that the Presto overestimates CD4 count in comparison to FACSCount, which is consistent with other studies comparing Presto to FACSCount or FACSCalibur [19–21, 23], though one study in Ethiopia did find a negative bias of 13.3 cells/μl when comparing Presto to FACSCalibur [16]. Overall, the accuracy of the Presto machine must be considered, since over-estimation of CD4 count could result in missing cases of advanced HIV disease, and overestimation of Hgb concentration could result in missed cases of anemia.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Reliable CD4 count testing is needed in health facilities to monitor the immune status of PLHIV, even as access to VL monitoring expands. This study found that the Presto overestimates CD4 count in comparison to FACSCount, which is consistent with other studies comparing Presto to FACSCount or FACSCalibur [19–21, 23], though one study in Ethiopia did find a negative bias of 13.3 cells/μl when comparing Presto to FACSCalibur [16]. Overall, the accuracy of the Presto machine must be considered, since over-estimation of CD4 count could result in missing cases of advanced HIV disease, and overestimation of Hgb concentration could result in missed cases of anemia.…”
Section: Resultssupporting
confidence: 91%
“…It has been validated previously against the BD FACSCalibur and BD FACSCount in several countries in Eastern and Southern Africa, predominantly in urban reference laboratory or hospital settings, with limited data on performance in rural settings. Its diagnostic accuracy was assessed in a district hospital, an advanced laboratory (Kenya Medical Research Institute/CDC) and in a community level facility in Kenya [8, 19, 21]; at an urban HIV clinic in Johannesburg, South Africa [22], at a hospital-affiliated HIV clinic in Harare, Zimbabwe [20], at a secondary hospital in Nigeria [23] and at four urban facilities in Ethiopia [16]; additionally, a multi-site evaluation took place in hospitals in Kenya, Thailand, San Francisco, and India [14], as well as in reference laboratories in Belgium and Tanzania [15]. Seven out of ten studies reviewed found that Presto over-estimated CD4 count when compared to the reference standard (FACSCount or FACSCalibur).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further strengthening the results of our study, another study by Angira et al assessed the performance of the BD FACSPresto system and further evaluated its accuracy, stability, linearity, precision, and reference intervals using capillary and venous blood of HIV-positive patients from Kenya; the Deming regression slopes for AbsCD4 and CD4% (venous/capillary) were within 0.97–1.03 and R 2 was ≥ 0.96; while slope and R 2 values were ≥ 0.94 for Hb 26 . Furthermore, in line with several previously published studies 23 , 26 , 31 , 32 , Bland–Altman analyses demonstrated close agreement between the BD FACSPresto system and the reference standards for all study participants. A notable advantage of the BD FACSPresto system is that testing can be performed using the finger-prick (capillary) blood sample without compromising the accuracy of analytical results, thus simplifying and improving the efficiency of diagnostics for HIV/AIDS.…”
Section: Discussionsupporting
confidence: 89%
“…Today, c-ART has been started for every patient diagnosed with chronic HIV infection independent of the CD4 + T lymphocyte count (10). Countries suffering a high HIV burden in sub-Saharan Africa are left with di cult decisions of when and how to implement the many new recommendations in resource-limited settings (19). Assessing the immune status in patients through POC CD4 + T lymphocyte count can identify advanced HIV disease, which should be prioritized for prophylaxis of opportunistic infections even if they are asymptomatic.…”
Section: Discussionmentioning
confidence: 99%